Palm Leaves Manuscripts in Kerala and their Preservation: Factors necessitating digital archiving - Mohamed Sageer T. K. and A.T. Francis (International Journal of Scientific and Research Publications, 2014)
Palm leaves occupy a significant place among the manuscripts available in the state of Kerala. As in any part of the world, palm leaves were one of the main and important sources for writing before the advent of paper in the southern region of India. Due to the absence of a proper solution for the storage of data in bulk, over the past years, thousands of palm leaf manuscripts were perished even without retaining a copy or image for future use. Being a solution for the problem, a study was conducted to find out whether the digital archiving is a solution for preserving the contents of the palm leaf manuscripts and what are the prevailing issues in digitizing the manuscripts as a whole. This paper also discusses major reasons for the deterioration of palm leaf manuscripts, how they can be preserved and what are the factors necessitating the digital archiving.